2021
DOI: 10.3390/min11010070
|View full text |Cite
|
Sign up to set email alerts
|

The Anomalous Seismic Behavior of Aqueous Fluids Released during Dehydration of Chlorite in Subduction Zones

Abstract: Dehydration and fluid circulation are integral parts of subduction tectonics that govern the dynamics of the wedge mantle. The knowledge of the elastic behavior of aqueous fluid is crucial to understand the fluid–rock interactions in the mantle through velocity profiles. In this study, we investigated the elastic wave velocities of chlorite at high pressure beyond its dehydrating temperature, simulating the progressive dehydration of hydrous minerals in subduction zones. The dehydration resulted in an 8% incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This interconnected network of highly conductive fluid/melt could dominate the bulk conductivity of rock and mask the relatively resistive matrix made up of remaining mineral phases. Similarly, an interconnected network of fluids/melt also affects the shear modulus of the rock, reducing both compressional and shear wave velocities (Chantel et al, 2016;Freitas et al, 2017Manthilake et al, 2021a;Soustelle et al, 2014;Weidner et al, 2018). The concomitant reduction of seismic wave velocities and the seismic attenuation are considered as strong indications of the presence of a liquid phase.…”
Section: Implications For the Wedge-mantle Electrical Anomaliesmentioning
confidence: 99%
“…This interconnected network of highly conductive fluid/melt could dominate the bulk conductivity of rock and mask the relatively resistive matrix made up of remaining mineral phases. Similarly, an interconnected network of fluids/melt also affects the shear modulus of the rock, reducing both compressional and shear wave velocities (Chantel et al, 2016;Freitas et al, 2017Manthilake et al, 2021a;Soustelle et al, 2014;Weidner et al, 2018). The concomitant reduction of seismic wave velocities and the seismic attenuation are considered as strong indications of the presence of a liquid phase.…”
Section: Implications For the Wedge-mantle Electrical Anomaliesmentioning
confidence: 99%
“…Previous field magnetotelluric results confirmed that high-conductivity layers (HCLs), as the special weak zones, are widely distributed in the Earth's interior (McGary et al, 2014;Selway, 2015;Hata et al, 2017). Typically, the HCLs have a characteristic of abnormally low velocity on the basis of seismic sounding data (Selway and O'Donnell, 2019;Manthilake et al, 2021a). The electrical conductivities of geological samples at high temperatures and high pressures are required to invert the MT profiles.…”
Section: Introductionmentioning
confidence: 97%